The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/mao.0000000000001157
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Impairment in Dementia

Abstract: Objective Recent studies suggest an association between vestibular and cognitive function. The goal of the study was to investigate whether vestibular function was impaired in individuals with mild cognitive impairment (MCI) and Alzheimer’s disease (AD) compared to cognitively normal individuals. Study Design Cross-sectional study. Setting Outpatient memory clinic and longitudinal observational study unit. Patients Older individuals ≥ 55 years with MCI or AD. Age, gender and education-matched normal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 48 publications
3
112
0
6
Order By: Relevance
“…Altogether, these findings suggest that navigation performance is impaired at some degree in all patients with vestibular impairment [which has been postulated in previous research (12,13,20)] and that this impairment is more severe in PPPD patients, to the point that it can be identified at the individual level and differentiate PPPD subjects from non-PPPD subjects (Figure 6). This ability of CSE scores to discriminate subjects was the highest in Block C (the most challenging navigational task in our experimental protocol, and thus the most sensitive task for identifying navigational impairment).…”
Section: Spatial Navigation Impairment May Be a Key Feature Of Pppdsupporting
confidence: 67%
See 1 more Smart Citation
“…Altogether, these findings suggest that navigation performance is impaired at some degree in all patients with vestibular impairment [which has been postulated in previous research (12,13,20)] and that this impairment is more severe in PPPD patients, to the point that it can be identified at the individual level and differentiate PPPD subjects from non-PPPD subjects (Figure 6). This ability of CSE scores to discriminate subjects was the highest in Block C (the most challenging navigational task in our experimental protocol, and thus the most sensitive task for identifying navigational impairment).…”
Section: Spatial Navigation Impairment May Be a Key Feature Of Pppdsupporting
confidence: 67%
“…Navigational abilities have been explored in vestibular research, having found decreased performance in navigation in bilateral peripheral vestibular loss (12,19). Nevertheless, the interpretation of these findings has been questioned due to methodological issues and revisited (13,20), suggesting that there might be confounding variables involved, regarding cognitive and emotional aspects of patients. We believe that the confounding variable might indeed be the presence of PPPD.…”
Section: Introductionmentioning
confidence: 99%
“…The role of vestibular dysfunction in dementia has been raised by Previc () and Harun et al () have recently reported that bilaterally absent cervical vestibular‐evoked myogenic potentials (cVEMPs) were associated with a greater than three fold increase in the odds of suffering from Alzheimer's disease. A down‐regulation of M 1 receptors in the hippocampus following BVL supports the hypothesis that vestibular degeneration negatively affects the hippocampal cholinergic system.…”
Section: Discussionmentioning
confidence: 99%
“…The role of vestibular dysfunction in dementia has been raised by Previc (2013) and Harun et al (2016) have recently M 1 ACh receptor density 7 and 30 days following BVL in the hippocampal subregions (CA1, CA2/3, and the DG), as well as the whole hippocampus, whole caudate putamen and dorsal caudate putamen using beta-imaging autoradiography. Significant Area, Section, Area*Section and Day*Treatment effects (P 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that vestibular dysfunction is particularly debilitating for cognitive function in the elderly population (Bigelow and Agrawal 2015;Bigelow et al 2015) and this has led to speculation that it may be a contributing factor to the development of dementia (Previc 2013). In fact, Harun et al (2016) have recently reported that vestibular dysfunction, as indicated by abnormal vestibular-evoked myogenic potentials, is associated with an increased risk of Alzheimer's disease. Understanding the contribution of vestibular sensory input to the regulation of theta rhythm will be an important part of the ongoing investigation of the way that vestibular input contributes to cognitive function (see Besnard et al 2016 for a review).…”
Section: B Amentioning
confidence: 99%